Reactive adsorption of methylene blue on montmorillonite via an ESI-MS study - Nogueira, Francisco Guilherme Esteves (2009)
Catalytic and adsorptive behaviors of montmorillonite to remove methylene blue were investigated. The clay mineral showed high activity for the oxidation of methylene blue in presence of H2O2 and on removing the organic substrate through reactive adsorption as evidenced from Electrospray Ionization Mass Spectrometry (ESI-MS) data. Montmorillonite was characterized by atomic absorption, powder X-ray diffractometry, scanning electron microscopy coupled with energy dispersive spectroscopy, infra-red spectroscopy and surface area analyses. Results indicated a highly reactive surface with can be regenerated by H2O2, promoting heterogeneous catalytic reaction to oxidize organic compounds from aqueous medium without any previous treatment of the montmorillonite.